2003
DOI: 10.1002/he.123
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal and Implications for Policy and Research

Abstract: We need to recognize and to convince policymakers that excessive dependence on contingent appointments is detrimental to undergraduate learning, and especially so for the "at-risk" students, unable Ernst BenjaminThe authors of this volume agree that contingent faculty provide a substantial and increasing proportion of undergraduate instruction. They do not agree in their assessment of the implications of these facts. Their disagreements, however, are not as great as may initially appear. This is particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 6 publications
1
42
0
2
Order By: Relevance
“…Not only does the tenure-line faculty population become such a small majority as to be ineffectual in institutions, but also the prolific hiring of non-tenure-track faculty represents a change in mind-set regarding all faculty: disposable, outsourced, deprofessionalized, and lacking the protections of academic freedom (Burgan, 2006;Slaughter and Rhoades, 2004). To strengthen the institution of tenure, Benjamin (2003a and2003b) suggests a reduction in non-tenure-track faculty hires, and instead institutions should move toward various lines of tenure such as a teaching tenure track to increase the value of the teaching aspect of faculty work.…”
Section: Non-tenure-track Faculty As a Challenge Or A Solution To Tenurementioning
confidence: 98%
See 1 more Smart Citation
“…Not only does the tenure-line faculty population become such a small majority as to be ineffectual in institutions, but also the prolific hiring of non-tenure-track faculty represents a change in mind-set regarding all faculty: disposable, outsourced, deprofessionalized, and lacking the protections of academic freedom (Burgan, 2006;Slaughter and Rhoades, 2004). To strengthen the institution of tenure, Benjamin (2003a and2003b) suggests a reduction in non-tenure-track faculty hires, and instead institutions should move toward various lines of tenure such as a teaching tenure track to increase the value of the teaching aspect of faculty work.…”
Section: Non-tenure-track Faculty As a Challenge Or A Solution To Tenurementioning
confidence: 98%
“…First, academics like Benjamin (2003a and2003b) and Finkin (1996) view the increase of non-tenure-track faculty as another means of weakening or perhaps removing tenure and whittling away at faculty autonomy and academic freedom. Second, academics such as Amacher and Meiners (2004) see tenure as an outdated practice that needs either drastic restructuring or complete removal (making everyone nontenure track to some extent).…”
Section: Non-tenure-track Faculty As a Challenge Or A Solution To Tenurementioning
confidence: 99%
“…Teaching, research, and service are often referred to as the triad or the three-legged stool that define the activities of university faculty (Popovich & Abel, 2002). Contingent faculty are referred to as faculty who are not typically on a tenure-track system (Benjamin, 2003;Gappa et al, 2005;Umbach, 2007). Although previous research examined the increasing use of contingent faculty across the academy, little work has been done to compare actual performance in teaching, research, and service among contingent, tenured, tenure-track, and no tenure system faculty.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they have very little time, and more often no place to meet with students outside of class (Wirt, et al, 2014). Adjunct faculty may also be less prepared to advise students on curriculum, degree requirements and college policies (Benjamin 2003b, Jolley, et al, 2015). …”
Section: Institutional Factorsmentioning
confidence: 99%
“…Poor institutional assimilation by part-time faculty can adversely affect student learning (Green, 2007). The effects included reduced instructional quality, lack of curricular cohesion, and weak advising (Benjamin, 2003a(Benjamin, , 2003b). Harrington and Schibik (2001) found that freshman who took a higher percentage of courses with part-time faculty members were less likely to persist towards their degree.…”
Section: Institutional Factorsmentioning
confidence: 99%